Tumble bumble - Bond, Felicia (New York Scholastic, 1996)
As a tiny bug walks along, he is joined by a cat, a crocodile, a pig, and other animals, all of which end up in a boy's bed
Keywords: Animals -- Fiction; Stories in rhyme